Exploring the Determinants of Intention to Quit and Awareness Regarding Ill Effects and Control Policies of Tobacco among Health Workers of a Tertiary Care Hospital in North India - Nidhi Prasad; Dharamvir Ranjan Bharati; Sanjay Kumar Choudhary; Binay Kumar (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Sociodemographic factor, awareness of the health effects and legislative law can lead to an increase in cessation of tobacco. Tobacco related knowledge and awareness are found to be better in people working in the health care sector as compared to the general population. The objective of the study was to find the prevalence of quitting rate amongst the health workers and perceived harmful effects on health, tobacco types and awareness of the anti -smoking legislation law in India among the health care workers working in a tertiary care hospital. Methods: A cross-sectional study was conducted among 306 hospital staff (196 housekeeping staff and 110 nursing orderlies) at a tertiary care hospital of Faridabad in 2018. Convenience sampling was conducted, and data were collected through pre tested semi structured questionnaires on sociodemographic details, awareness of ill effects of tobacco and intention to quit. Results: Among 133 current tobacco users, intention to quit smoking was present in only 96 respondents (72.18%). There was association between age, marital status and type of family with the intention to quit. 63 respondents (21%) were unaware that smoking causes lung cancer and 115 (38%) of the total respondents did not consider smokeless tobacco as a causal risk factor for cancer. A total of 180 respondents (58.8%) were not aware of anti-tobacco control laws in India. Moreover, it was found that health concern was commonest reason of intention to quit. Conclusions: Intention to quit tobacco among study participants was low, so there is need to look for knowledge gaps about harms of different types of products and anti-tobacco legislation. More comprehensive tobacco cessation services should also be prioritized in the heath sector.Keywords: awareness of ill effects, COTPA, India, intention to quit, tobacco